(untitled) (Al-Academy, 2022)
The visual stimulus is the effective force in visual attraction that achieves visual and perceptual co-optation and is important in wooing the recipient, and many procedural processes in the design are interpreted on it as the visual stimulus achieves visual comfort and a sense of pleasure and gives (place) the interior space a transformation in its plastic structure as well as arousing attention through The kinetic rhythm and the formal diversity, which increases the possibility of breaking the routine and traditional constraints of design patterns through the coating and encapsulation of the vertical and horizontal levels . Thus, the research problem was launched based on the following question: What are the stimuli of the visual stimulus in the designs of the internal space of the communications company (Zain Iraq)? In order to achieve the goal of the current research represented by revealing the visual stimulus in the designs of the internal space of the telecom company Zain Iraq. In order to cover the contents of the research and its variables, the research structure is distributed into three chapters. The first set out to clarify the introductory framework for the research, while the second reviewed the theoretical framework and the reality of two chapters, namely:1. The visual stimulus as a concept in interior design.2. The relationship of the visual stimulus in the design of the interior space.The third chapter deals with the research procedures, results and conclusions, including